Malaysian children's interactions on the prevalence of road safety : a case study in primary schools in Kelantan. - Shahrimin, Mohamad Ibrani; Hashim, Ahmad Hariza (Institut Sosial Malaysia, 2010)
This paper reported the study on verbal interactions of Malaysian children in relation to the prevalence of their major road safety psychological domain attributes. The respondents consist of primary school children with the age-range of 7 to 9 years old in Kelantan. In this study, Road Safety Educational Kit (RSEK) was distributed and implemented into the teachings of 25 primary schools in Pasir Mas and Tanah Merah, Kelantan Darul Naim. Pre-experimental-post-test design was utilised to measure the participants’ major domain of psychological attributes on road safety. This study indicates gender difference may have an impact on the level of road safety knowledge. Appropriate approach towards different levels of knowledge, attitude and practice on the exposure road safety learning were also found to be prevalent among children.